3-D negotiation : powerful tools to change the game in your most important deals - Lax, David A.; Sebenius, James K., 1953- (Boston, Mass. : Harvard Business School Press, 2006)
"In 3-D Negotiation: Powerful Tools to Change the Game in Your Most Important Deals, David Lax and James Sebinius urge bargainers to look beyond tactics at the table. Indeed, persuasive tactics are only the "first dimension" of the author's 3-D Negotiation (TM) approach, developed from their decades of doing deals and analyzing great dealmakers." "Packed with practical steps and engaging examples, 3-D Negotiation demonstrates how superior setup moves plus insightful deal design can enable you to reach remarkable agreements once you arrive at the table - deals that would be unattainable by standard tactics, no matter how skillful."--Jacket.
Overview: 3-D negotiation in a nutshell -- Negotiate in three dimensions -- Do a 3-D audit of barriers to agreement -- Craft a 3-D strategy to overcome the barriers -- Set up the right negotiation, "away from the table" -- Get all the parties right -- Get all the interests right -- Get the no-deal options right -- Get the sequence and basic process choices right -- Design value-creating deals, "on the drawing board" -- Move "northeast" -- Dovetail differences -- Make lasting deals -- Negotiate the spirit of the deal -- Stress problem-solving tactics, "at the table" -- Shape perceptions to claim value -- Solve joint problems to create and claim value -- 3-D strategies in practice: "let them have your way" -- Map backward to craft a 3-D strategy -- Think strategically, act opportunistically.
Includes bibliographical references (pages [255]-267) and index.
Description based on print version record.
Keywords: Negotiation in business; Négociations (Affaires); Negotiation in business; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books